The Image of Bluebeard in the Age of Symbolism - Olga S. Pospelova (Литературный факт, 2022)
The article examines the symbolics in the play “Ariana and Bluebeard, or Vain Deliverance” (1896) by the Belgian writer Maurice Maeterlinck and in the libretto “Duke Bluebeard’s Castle” by the Hungarian writer Béla Balazs (1911). There is a transformation of the Bluebeard story from folklore to the field of symbolist and neo-romantic literature, where it undergoes significant changes, being transformed into a “new age myth.”